Occupational stress and its effects on security personnel performance : a case study of Safeguards G4S - Jebid Arif bin Sengorou
Occupational stress is stress related to one's job. Occupational stress often stems from unexpected responsibilities and pressures that do not align with a person's knowledge, skills, or expectations that leads to discomfort and decline in the quality of work. This study was conducted to examine the relationship between occupational stress and its effects on security personnel performance. A total of 100 respondents which consists of SG4S security personnel from various positions and departments has been participated in this study by answering an online survey questionnaire. Demographic data and the three (3) main variables which includes causes of occupational stress, factors affecting security personnel performance, and stress impact on security personnel performance were measured to analyse the relationship between occupational stress and its effects on security personnel performance. Data obtained were tabulated and calculated using SPSS version 24.0. Analysis of the demographic data shows that majority of the respondents were male (70%), 59% with married status. Three quarter (75%) of the respondents were aged 30 years and above. 60% of them only poses SPM as the highest education level, hold non-executive post in the company, and received lowest rate of monthly income, respectively. There is no significant different of the total stress score between male and female respondents. However, there is a significant linear relationship between position (p<0.001) and monthly income (p=0.001) with occupational stress. The findings in this study revealed that there is a significant negative linear correlation between occupational stress and security personnel performance (r = – 0.77). Finally, occupational stress is triggered by many factors that may lead to negative impact on security personnel performance.